ANALISIS PENDAPATAN PETANI KELAPA SAWIT RAKYAT DI KECAMATAN SUNGAI APIT KABUPATEN SIAK - Mega Oktovianti; Yusmini '; Didi Muwardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research aims to (1) figure out and analyze the level of nett income from the oil palm small holders in Sungai Apit Sub-district Siak Regency, (2) figure out and analyze the comparizon of efficiency level towards the oil palm small holders in Category I and Category II in Sungai Apit Sub-district and Siak Regency, and (3) figure out the problems faced by the independent oil palm small holders. The survey method was used in the research, and the sampling method was purpossive sampling method. 15 respondents as the sample were taken from Category I, and 15 other respondents as the sample were taken from Category II. The result has shown that the oil palm farming run by both of Categories are profitable, with the average of nett income from the small holders in Category I was Rp. 15.611.225,23/ha/year and the average of nett income from the small holders in Category II was Rp.22.340.469,82/ha/year. The average score of RCR for the small holders in Category I was Rp 2.42, while the small holders in Category II was Rp 2.49. From the t test it was obtained that the t score was smaller than from the table. It meant that the nett income earned by the oil palm small holders in Category I was not significantly different than the nett income of the oil palm small holders in Category II. The problems that were faced by the oil palm small holders were the lack of guidance, production facilities, and pest. Keywords: nett income, RCR, problems of the oil palm small holders